Replacement of dietary groundnut-cake by soybean-meal supplemented with dlmethionine on the performance of layer chickens - NAULIA, UMA; SINGH, K S (The Indian Journal of Animal Sciences, 2014)
Single comb White Leghorn hens (90) of 24 week-old (average B Wt. 1200Â±20g) were divided in a completely randomised design for S treatments with 3 replicates of6 bird each. The birds were fed on diets containing groundnul. cake (GNC) replaced by soybcanÂ·meal (SBM) supplemented with DL-mcthionine. The GNC was replaced by SBM (on nitrogen basis) at 0, 25. 50. 75 and 100% levels. The percent hen-day egg production at 75% replacement level was significantly higher (P